KEANEKARAGAMAN JENIS IKAN KARANG DI PULAU BADI DAN PULAU KODINGARENG LOMPO - Dahlan, Muh. Arifin; Andiewati, Suci; Omar, Sharifuddin Bin Andy; Nur, Muhammad (Hasanuddin University, 2015)
The research aim is to know the diversity of coral fish in Badi and Kodingareng Lompo islands. The study isheld from May until June 2014. The samples are taken twice for one month by using belt transect method.Transect lines were put on depth 3 meters and each dept was. The observed region is as long 50-meter transectlines with the shoreline margin 2,5 meter at the left and right side of the transect. Analysis of data isdone by calculating the kinds of compositions, abundance, diversity index, uniformity, and domination. Theresult of this research is the composition of coral fish in each island. In Badi islands the composition of coralfish is 50 kinds of fish from 15 families with 131 fish. In Kodingareng Lompo island, the composition of coralfish is 21 kinds of fish from 9 families with 82 fish. In Badi island , the diversity index is 3.3870 andKodingareng Lompo island is 2.5566, the uniformity index Badi island is 0.2606 and Kodingareng Lompoisland is 0.2527, and the dominantion index Badi island is 0.0461 and Kodingareng Lompo island is 0.0967.Keywords: Diversity, Abundance, Coral fish, Badi island, Kodingareng Lompo island